Eosinophilic esophagitis: literature review and original case presentation - V. T. Ivashkin; Ye. K. Baranskaya; V. O. Kaybysheva; Ye. V. Ivanova; Ye. D. Fedorov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2012)
The aim of publication. To show features of clinical pattern, difficulties of diagnostics and treatment of eosinophilic esophagitis at the example of clinical case.Features of clinical case. In young patient the diagnosis of eosinophilic esophagitis at stage of complications (esophageal stricture) has been made 20 years after manifestation of disease. Conservative treatment by topical corticosteroids did not result in resolution of dysphagia and morphological changes of esophageal wall that required a course of systemic corticosteroids with further dilatation of the esophagus recommended to the patient. Poor knowledge of this disease by internists and endoscopists often results in establishment of incorrect diagnoses, late diagnostics, development of complications requiring surgical interventions, decrease of quality of life of patients.Conclusion. Eosinophilic esophagitis is chronic immune antigen-mediated inflammatory disease of the esophagus with still obscure etiopathogenesis. Diagnostics is based on characteristic clinical pattern of dysphagia that is always combined to eosinophilic infiltration of esophageal mucosa at histological study. Treatment options of eosinophilic esophagitis are limited now and include strict eliminative diet and application of steroid hormones.